Higher education cooperation at the regional level - Jane Knight (Emerald Publishing, 2024)
Purpose - This article focuses on regional-level cooperation in higher education by examining the functional, organizational and political approaches (FOPA) framework for higher education regionalization and using supra-national regional universities as established and successful examples of regional-level higher education cooperation among countries. Design/methodology/approach - A conceptual framework is used to provide the structure for analyzing the key approaches to higher education regionalization, followed by an analysis of supra-national regional universities to demonstrate the application of the model. Findings - The FOPA framework for higher education regionalization includes three approaches. The first is the functional approach, which includes both collaborative academic and research activities among higher education institutions as well strategies and policies to help align systems across a region. The second is the organizational approach, which focuses on networks, organizations, institutions and programs, which facilitate partnerships. The third is the political approach, which includes regional-level agreements, declarations and strategic plans to promote higher education collaboration. Key higher education activities for each approach are discussed in generic terms, with examples provided from major regions of the world. Research limitations/implications - The research was based on desk research only. No interviews were conducted. Practical implications - A conceptual analysis and a model were provided for the concept of regionalization of higher education and for regional universities, which can help readers locate their interests and research in the regionalization of higher education. Examples of three different types of regional universities were provided to give concrete illustrations of a regional university. Social implications - One of the rationales driving regional universities is to address and increase a sense of regional identify and to meet the social, economic and educational needs of the specified region. Originality/value - Regional universities, such as the University of West Indies, Arab Open University and the Pan-Africa University, are an understudied phenomenon. Using them as innovative and sustainable examples of higher education regional cooperation and the FOPA model, this study illustrates how single-campus, multiple-campus and virtual regional universities are functioning to meet the diversified needs and priorities across a region through cooperation among countries.